The effect of two novel C-type lectins, Ba100 and Ba25, isolated from the venom of the puff adder, Bitis arietans on T lymphocyte proliferative responses - Spearman, Catherine Wendy Nest (Department of Medicine, 2014)
Includes abstract. Includes bibliographical references (p. 233-318).